AHP 28: Review: Drokpa - Ligaya, Beebe (Asian Highlands Perspectives, 2018)
Daniel J. Miller is a rangeland ecologist who has studied agricultural and pastoral practices around the Himalayas and on the Tibetan Plateau since the 1970s. Drokpa: Nomads of the Tibetan Plateau and Himalaya is a collection of photographs published for a general audience. The text's stated purpose is to reach beyond the "restricted readership" of Miller's academic publications and to "[provide] the viewers with a more considerate and compassionate portrait of Tibetan nomads" (6-7). ...